A two‐dimensional, two‐level framework for achieving corporate sustainable development: Assessing the return on sustainability initiatives. (6th April 2018) - Wu, Lin; Subramanian, Nachiappan; Gunasekaran, Angappa; Abdulrahman, Muhammad Dan‐Asabe; Pawar, Kulwant Singh; Doran, Des
Abstract: Sustainability studies in operations management have reported the positive effects of lean, green and social management systems on various dimensions of a firm's sustainability performance. However, despite its importance and relevance, the time dimension of sustainability has not been systematically considered. This paper recategorizes the well‐identified sustainability initiatives based on a time dimension and empirically validates the categorization. Structural equation modeling analyses were performed using data collected from 284 Chinese automotive firms. The results suggest that various lean and reactive green practices can be categorized as "short‐term sustainability initiatives" because the effects of implementing these practices can be seen in a short time. Specifically, the benefits of implementing short‐term sustainability initiatives can be further strengthened and reinforced in the long run by implementing corporate social responsibility (CSR) practices. In addition, our findings demonstrate that to fully realize the potential associated with CSR practices, firms need to be orientated to the long term and adopt a wait and watch approach.